PEMANFAATAN MEDIA BONEKA TANGAN SEBAGAI STRATEGI PENINGKATAN KEMAMPUAN BERBAHASA ANAK USIA 4–5 TAHUN DI TK PUTRA BANGSA GADING - Munawaroh, Searul; Indah Kharismawati; Trio Suwargono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve the language abilities of children aged 4–5 years through the use of hand puppet media. The research employed a two-cycle Classroom Action Research design involving 20 children at Putra Bangsa Gading Kindergarten, Probolinggo. Data were collected through structured observations based on receptive and expressive language indicators and analyzed using descriptive quantitative techniques with percentage analysis. The results showed that in the pre-cycle phase, 55.0% of children were in the Not Yet Developed category, 30.0% were Beginning to Develop, and 15.0% were Developing as Expected. In Cycle I, improvement was observed, with 55.0% of children in the Beginning to Develop category, 40.0% in Developing as Expected, and 5.0% in Very Well Developed. A significant increase occurred in Cycle II, where all children (100%) reached at least the Developing as Expected category, consisting of 55.0% Developing as Expected and 45.0% Very Well Developed. These findings indicate that the use of hand puppet media is effective in enhancing the language abilities of kindergarten children.